Phytoremediation: Kiambang (Salvinia molesta) Reduces Batik Dye Waste Pollutants as a Learning Resource on Environmental Pollution - Surahman, Endang; Ali, Mufti; Suharsono, Suharsono (Bioedusiana: Jurnal Pendidikan Biologi, 2025)
The dyeing process in the batik-making process uses many dyes containing various substances that can be harmful pollutants for humans and other biota. However, various organisms can reduce pollution's effects with the principle of remediation, especially those carried out by several plants. One type of plant that has the potential as a bioremediator is the kiambang plant (Salvinia molesta). This study aimed to determine the effect of kiambang (Salvinia molesta) in reducing batik dye waste pollutants as a learning resource for environmental pollution. This study was an experimental study, with the method used being descriptive analysis. Two treatments were used: the treatment of different kiambang weights in the same waste concentration and the treatment of the same kiambang weight in different liquid waste concentrations. The study was conducted at the Botany Laboratory of the Department of Biology Education, Faculty of Teacher Training and Education, Siliwangi University, for six months. The tools used in this study included a 40-liter incubation container, a balance, a measuring cup, a thermometer, and a pH meter. Meanwhile, the materials used in this study were batik liquid waste from batik artisans in the Cigeureung Village, Tasikmalaya City, and the Kiambang plant. Data collection was carried out by observing the growth of kiambang in 4 observations within 10 days. Data analysis was carried out based on the physical and chemical properties of wastewater, with various indicators such as acidity/pH, total suspended solids, BOD, COD, phenol content, total chromium content, total ammonium content, sulfide content, cadmium, mercury, and nickel. Chemical analysis was carried out at PT. Sucofindo (Persero) is located at Jalan Soekarno Hatta No. 217, Bandung. Based on the analysis and testing of various indicators, it is known that the kiambang plant can reduce various chemical pollutant contents in wastewater in both treatments. Based on these results, it can be concluded that the kiambang plant can reduce pollutants in batik dyeing wastewater samples at the Cigeureung Batik Center, Cipedes District, Tasikmalaya City.